The impact of explicit pragmatic instruction on L2 suggestion-making across task complexity - Márquez, Daniel; de Graaff, Rick (Studies in Second Language Learning and Teaching, 2026)
Pragmatic competence, understood as the ability to use language effectively and appropriately in social interactions, is recognized as a critical component of second/foreign language (L2) development, yet questions remain about how it is shaped by instruction. This study examined the impact of explicit pragmatic instruction on the complexity and accuracy of English L2 learners’ production of suggestions, a directive speech act that balances influence and listener autonomy. Thirty-seven secondary school students with intermediate to advanced English completed interactive decision-making tasks of varying cognitive demands (simple vs. complex), accompanied by semi-structured interviews exploring whether they prioritized linguistic form or meaning conveyance, at three time points (pretest, immediate posttest, delayed posttest). Instruction involved three sessions integrating awareness-raising, input presentation, metapragmatic analysis, and interactive practice, which emphasized directness and politeness strategies for suggestion-making in different settings. Linear mixed-effects analyses indicated that instruction enhanced both pragmatic complexity and accuracy, with similar gains for simple and complex tasks. Higher-proficiency learners maintained more advanced performance, while lower-proficiency learners showed rapid post-instruction increases, particularly in complexity, narrowing the gap with their peers over time. Interviews suggested heightened learner agency, strategic decision-making, and sociopragmatic sensitivity following instruction. These findings underscore the effectiveness of explicit, reflective, socially grounded instruction for fostering context-sensitive pragmatic performance and highlight the importance of proficiency-sensitive approaches and post-instructional reinforcement for sustaining complex pragmatic behaviors across diverse communicative situations.